Source encoding with negacyclic codes. - Dion, Jean-Pierre. (University of Ottawa (Canada), 1977)
Following a brief review of existing source coding techniques, negacyclic codes are defined and a joint source and channel coding scheme making use of these codes is introduced. The distortionless case and cases where distortion is allowed, are examined from the point of view of data compression. An orthogonal variation on the original scheme is also introduced. Discrete memoryless sources are assumed throughout, and the metric used in all cases is the Lee distance.
Keywords: Engineering, Electronics and Electrical.